Check sibling questions
Chapter 7 Class 12 Integrals
Concept wise

Slide15.JPG

Slide16.JPG
Slide17.JPG
Slide18.JPG
Slide19.JPG

This video is only available for Teachoo black users

Solve all your doubts with Teachoo Black (new monthly pack available now!)


Transcript

Ex 7.8, 1 ∫1_π‘Ž^𝑏▒〖π‘₯ 𝑑π‘₯γ€— ∫1_π‘Ž^𝑏▒〖π‘₯ 𝑑π‘₯γ€— Putting 𝒂 =π‘Ž 𝒃 =𝑏 𝒉=(𝑏 βˆ’ π‘Ž)/𝑛 𝒇(𝒙)=π‘₯ We know that ∫1_π‘Ž^𝑏▒〖𝑓(π‘₯) 𝑑π‘₯γ€— =(π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) 1/𝑛 (𝑓(π‘Ž)+𝑓(π‘Ž+β„Ž)+𝑓(π‘Ž+2β„Ž)…+𝑓(π‘Ž+(π‘›βˆ’1)β„Ž)) Hence we can write ∫1_π‘Ž^𝑏▒〖π‘₯ 𝑑π‘₯γ€— =(π‘βˆ’π‘Ž) lim┬(nβ†’βˆž) 1/𝑛 (𝑓(π‘Ž)+𝑓(π‘Ž+β„Ž)+𝑓(π‘Ž+2β„Ž)+… +𝑓(π‘Ž+(π‘›βˆ’1)β„Ž) Here, 𝒇(𝒙)=π‘₯ 𝒇(𝒂)=π‘Ž 𝒇(𝒂+𝒉)=π‘Ž+β„Ž 𝒇 (𝒂+πŸπ’‰)=π‘Ž+2β„Ž … 𝒇(𝒂+(π’βˆ’πŸ)𝒉)=π‘Ž+(π‘›βˆ’1)β„Ž Hence, our equation becomes ∴ ∫_𝟎^𝒂▒𝒙 𝒅𝒙 = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) 1/𝑛 (𝑓(π‘Ž)+𝑓(π‘Ž+β„Ž)+𝑓(π‘Ž+2β„Ž)…+𝑓(π‘Ž+(π‘›βˆ’1)β„Ž)) = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) 1/𝑛 (π‘Ž+(π‘Ž+β„Ž)+(π‘Ž+2β„Ž)+ …+(π‘Ž+(π‘›βˆ’1)β„Ž)) = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) 1/𝑛 ( 𝒂+𝒂+ …+𝒂 +β„Ž+2β„Ž+ ……+(π‘›βˆ’1)β„Ž) = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) 1/𝑛 ( 𝒏𝒂 +β„Ž+2β„Ž+ ……+(π‘›βˆ’1)β„Ž) = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) 1/𝑛 ( π‘›π‘Ž+β„Ž (𝟏+𝟐+ ………+(π’βˆ’πŸ))) 𝒏 π’•π’Šπ’Žπ’†π’” We know that 1+2+3+ ……+𝑛= (𝑛 (𝑛 + 1))/2 1+2+3+ ……+π‘›βˆ’1= ((𝑛 βˆ’ 1) (𝑛 βˆ’ 1 + 1))/2 = (𝒏 (𝒏 βˆ’ 𝟏) )/𝟐 = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) 1/𝑛 ( π‘›π‘Ž+(𝒉 . 𝒏(𝒏 βˆ’ 𝟏))/𝟐) = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) ( π‘›π‘Ž/𝒏+𝑛(𝑛 βˆ’ 1)β„Ž/2𝒏) = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) ( π‘Ž+(𝑛 βˆ’ 1)𝒉/2) = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) ( π‘Ž+(𝑛 βˆ’ 1)(𝒃 βˆ’π’‚)/(2 . 𝒏)) = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) ( π‘Ž+(𝒏/𝒏 βˆ’ 𝟏/𝒏) ((𝑏 βˆ’ π‘Ž) )/2) [π‘ˆπ‘ π‘–π‘›π‘” β„Ž=(𝑏 βˆ’ π‘Ž)/𝑛] = (π‘βˆ’π‘Ž) (π‘™π‘–π‘š)┬(π‘›β†’βˆž) ( π‘Ž+(πŸβˆ’ 𝟏/𝒏) ((𝑏 βˆ’ π‘Ž) )/2) = (π‘βˆ’π‘Ž)( π‘Ž+(1βˆ’ 𝟏/∞) ((𝑏 βˆ’ π‘Ž) )/2) = (π‘βˆ’π‘Ž)( π‘Ž+(1βˆ’πŸŽ) ((𝑏 βˆ’ π‘Ž) )/2) = (π‘βˆ’π‘Ž)( π‘Ž+ (𝑏 βˆ’ π‘Ž )/2) = (π‘βˆ’π‘Ž)((2π‘Ž + 𝑏 βˆ’ π‘Ž )/2) = (𝑏 βˆ’ π‘Ž)(𝑏 + π‘Ž)/2 = (𝒃^𝟐 βˆ’ 𝒂^𝟐)/𝟐

Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 12 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.